(untitled) (Journal of Governance and Development (JGD), 2023)
The objective of this paper is to interrogate the nexus between incumbency factor, internal party democracy and democratic consolidation in Nigeria’s Fourth Republic. Abundance evidence suggest that Incumbency factor and internal party democracy exercise monumental influence on the growth of democracy in Nigeria. The paper adopts a conceptual and qualitative methodology. The researcher collected the data through the secondary sources. Thus, relevant materials including textbooks, journal articles, party constitutions and the 1999 constitution of Nigeria were consulted in the quest to establish the linkages. The assertion was substantiated and buttressed by the data. The research unveiled that abuse of incumbency advantage and lack of internal party democracy constitute major drawbacks to democratic consolidation in Nigeria. Adducing convincing evidence, the paper established `the relationship between incumbency factor, internal party democracy and democratic consolidation in Nigeria. The paper is particularly imperative for stakeholders in Nigeria’s democratic experience as it would make them to be conscious and refrain from abuse of incumbency and adhere to the doctrines of internal party democracy in order to fast track democratic growth and consolidation in Nigeria.